Pengaruh Metode Bernyanyi Terhadap Daya Ingat Anak Materi Tanaman Atau Binatang - Nuraenisah, Siti; Nirmalasari, Omis; Komariah, Siti Laela; Adha, Maghfira Hikmatul (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE EFFECT OF SINGING METHOD ON CHILDREN'S MEMORY OF PLANT OR ANIMAL MATERIAL This study aims to analyze the influence of singing as a method to improve memory retention among early childhood learners in learning about plants and animals at PAUD Mutia Bunda. The main issue addressed is the low memory performance in children due to traditional, less engaging teaching methods. The research was conducted using classroom action research across two cycles with both qualitative and quantitative approaches. Data were collected through observation, oral tests, and questionnaires given to teachers and parents. The results show that singing, combined with gestures and visual aids, significantly enhanced memory retention, with average scores rising from 72.3 in the first cycle to 81.6 in the second. The percentage of children achieving the minimum score of 75 also increased from 60% to 86.7%. It can be concluded that singing is an effective strategy to strengthen memory in early learners for thematic content. The implications of this finding include the reinforcement of multimodal learning theory, practical adoption of music-based teaching in resource-limited preschools, and further development of arts- and culture-integrated curricula.